Efektivitas Komunikasi Pemerintah Daerah Dalam Penagihan Tunggakan Pajak Usaha Kabupaten Nabire - Muhammad Thoyyib Ramadhan; Usman Arfan (Jurnal Teknologi dan Informatika, 2025)
This study develops a web application to facilitate employees of the Regional Revenue Agency in Nabire Regency for taxpayer registration, payment reminders, and monitoring business tax arrears. The research uses a descriptive qualitative approach with data collected via observation, interviews, and documentation. The application development follows a systematic Waterfall model. Results show that the application improves data access, speeds communication between government and taxpayers, and aids real-time arrears monitoring, potentially enhancing business tax collection effectiveness.